Analysis and design of two-way slabs strengthened in flexure with FRCM. (1st April 2022) - Kadhim, Majid M.A.; Jawdhari, Akram; Adheem, Ali Hadi; Fam, Amir
Highlights: The behavior of two-way RC slabs strengthened with FRCM system is studied. A three-dimensional FE model is developed and verified with experimental results. Studied FRCM coverage area, discontinuous FRCM strips; slab reinforcement ratio, concrete strength, and slab aspect ratio. Two existing analytical models were evaluated and found to be unconservative or insensitive to key parameters. A regression analysis was performed and resulted in two expressions for FRCM effective strain and better predictions for ultimate load. Abstract: Fabric reinforced cementitious mortar (FRCM), an emerging sustainable retrofit technique, has seen very limited research and applications on two-way reinforced concrete (RC) slabs. In this study, a three-dimensional finite element (FE) model is developed for FRCM-strengthened slabs, incorporating concrete nonlinearity, cracking, debonding and rupture. After validation with experimental results from literature, an extensive parametric study was performed, examining the effects of FRCM coverage area as a ratio of the width of FRCM reinforcement ( wFRCM )-to-span ( S ); the use of discontinuous FRCM strips; internal steel reinforcement ratio ( ρs ); compressive strength of concrete ( f ′c ); and aspect ratio of slab (α). The study showed that ultimate strength ( Pu ) increases sharply by 84% as ( wFRCM / S ) increased from zero to 0.25, then only by 19% from ( wFRCM / S ) of 0.25 to 1.0. In general, Pu increased with f ′c and ρs but was not affected by α. Two existing models were evaluated and found to be unconservative or insensitive to key parameters. A regression analysis was performed on data from the parametric study, resulting in two expressions for the FRCM effective strain ( εfe ) and much better predictions for Pu .